The Analysis of University Sustainable Transportation Driving Factors - Putri, Rachmaning Tyas Yoga (Efficient: Indonesian Journal of Development Economics, 2021)
Sustainable transportation is a means of transportation implemented by UGM and UII whose policies are stated in the Strategic Plan of each University. This sustainable transportation is implemented as a form of Green Campus. This study aimed to determine the factors driving the selection of Sustainable Transportation in the UGM and UII areas. This type of research used a quantitative approach. The types of data used in this research were primary data and secondary data. The data collection method in this research used the questionnaire method distributed to 200 respondents consisting of students, lecturers and staff in each university. The data analysis method used was the factor analysis method to find the driving factors for sustainable transportation, namely convenience, health, benefits, costs, weather, security, reliability, travel time, convenience, and routes. The results of this study found 3 factors which drove the sustainable transportation, namelys of efficiency, consisting of reliability, travel time, convenience, and routes, facility factors consisting of safety, benefits, health and comfort, and non-physical factors, consisting of weather and costs. Transportasi Berkelanjutan merupakan sarana transportasi yang diterapkan oleh Universitas Gadjah Mada dan Universitas Islam Indonesia yang kebijakannya tertera pada Renstra masing-masing Universitas, Transportasi Berkelanjutan ini diterapkan sebagai wujud dari Green Campus. Penelitian ini bertujuan untuk mengetahui faktpr pendorong pemilihan Transportasi Berkelanjutan di kawasan Universitas Gadjah Mada dan Universitas Islam Indonesia. Jenis Penelitian ini menggunakan pendekatan Kuantitatif. Jenis data yang digunakan dalam penelitan ini adalah data primer dan data sekunder. Metode pengumpulan data dalam penelitian ini adalah dengan metode Kuisioner dan disebarkan ke 200 responden yang terdiri dari mahasiswa, dosen dan tendik di masing-masing unniversitas. Metode analisis data yang digunakan metode analisis faktor untuk menemukan faktor pendorong Transportasi Berkelanjutan yaitu Kenyamanan, Kesehatan, Keuntungan, Biaya, Cuaca, Keamanan, Keandalan, Waktu Tempuh, Kemudahan, dan Rute. Hasil Penelitian ini menunjukan 3 faktor yaitu Faktor Efisiensi yang terdiri dari Keandalan, Waktu Tempuh, Kemudahan, dan Rute. Faktor Fasilitas yang terdiri dari Keamanan, Keuntungan, Kesehatan dan Kenyamanan. Faktor ketiga yaitu Faktor Non Fisik yang terdiri dari Cuaca dan Biaya.